Admix'em: a flexible framework for forward-time simulations of hybrid populations with selection and mate choice. (28th November 2015) - Cui, Rongfeng; Schumer, Molly; Rosenthal, Gil G.
Abstract : Summary: We introduce a new forward-time simulator, Admix'em, that allows for rapid and realistic simulations of admixed populations with selection. Complex selection can be achieved through user-defined fitness and mating-preference probability functions. Users can specify realistic genomic landscapes and model neutral SNPs in addition to sites under selection. Admix'em is designed to simulate selection in admixed populations but can also be used as a general population simulator. Usage and examples are in the supplement. Availability and Implementation: C ++ and OpenMP, supports 64-bit Linux/Unix-like platforms. https://github.com/melop/admixem . Contact: rcui@age.mpg.de Supplementary information: Supplementary data are available at Bioinformatics online.